Perbaikan Proses Produksi Menggunakan ECRS Based Line Balancing pada Lini Perakitan Stator 4 - Oksiana Tiovani; Fakhrina Fahma (Performa: Media Ilmiah Teknik Industri, 2019)
PT. XYZ is one of the manufacturing companies in Indonesia. The company produces water pumps. An important component in the water pump is the stator. The observation results in the Stator Assembly line 4 show that low line efficiency occurs because the production process has not run optimally. So that an improvement in the production process is important to do on this line. One method to improve the production process is ECRS based line balancing. By still considering the concept of line balancing, line efficiency can be improved through improving the production process. Through the improvement of the production process, there was a decrease in the number of work stations from 10 work stations to 9 work stations, improvement of line layout and 7th work station (Heating Air Dryer), also an increase in line efficiency from 74.72% to 81.09%.